Safeguard Of People’s Rights Under The African Court: Challenges And Resolve - Egbara Owa, Ph.D, Owa; Ikechukwu Ugwuerua, Ph.D, Emmanuel; Joy Ucha Egwu, Ph.D, Mrs.; Egbara Owa, M.Sc, Wisdom (International Journal of Psychosocial Rehabilitation, 2020)
The African Human Rights Court was established on January 25, 2004. The paper is aimed at examining the development of the Court both on normative and institutional approaches, because these have resultant impacts on the African Court. Major among other impacts is the transformation of the Organization of African Unity (AU), which adopted and created the Court of Justice. The objective of the paper is the examination of the developments of the Court, with particular focus on the determination of the place of the African Court within the context of the African Union and the auxiliary impact it created thereafter. Meanwhile, the Constitutive Act of the Union is silent on the welfare of the African Human Rights Commission; rather, it convertly established the African Court of Justice. At its creation, the composition of the Court was yet to be determined since its establishing protocol, which was to compliment the mandate of the commission, was yet to be agreed upon. Irrespective of the above infelicities, the Court has the potency of better protecting people’s rights required. It promotes the resultant outcome on human rights issues from its inception as it makes recommendations and binding decisions. The establishment of the African Court of Justice gave birth to a novel epoch of liberation in handling cases of human rights, which was opposed to the secrecy that beclouded the proceedings of the Commission due to its restrictive preservative approach as a requirement to the prosecution of human rights cases. The composition of the Court stands out as one of its banes because its Justices are appointed, but the president who is appointed to serve on a part-time basis. This methodology underscored the integrity bestowed on the Court. In conclusion, it was stated that the merger of both the Human Rights Commission and the Court on Human and Peoples’ Rights could promote the rights of African citizens and provide accommodations for the shortcomings of the criteria in the charter on which the Court is established. A call for the merger to be seen from the perspective of administrative convenience was recommended to facilitate distribution only to avoid jeopardizing the effort and/or energy that was invested in creating the Court.